2016
DOI: 10.17795/ijpbs-3813
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Fear of Exposure to Sharps in Nurses

Abstract: BackgroundInjuries caused by sharp objects, which involve biological hazards are considered as one of the most important factors that lead to stress among the nursing staff. Contact with sharp objects is a major concern among healthcare workers, especially nurses.ObjectivesThis study was done to determine the amount of stress caused by exposure to sharp medical instruments among nurses.Materials and MethodsThis was a cross-sectional research on 527 nurses, working at different medical centers across Iran, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
2
10
0
2
Order By: Relevance
“…In agreement with a study done by Nayak et al (19) , who revealed that even with the The present study results were accordance with Moayed et al (28) study who reported that the level of stress among nurses are extremely multiplied by working with sharp objects. In agreement with study Tanta Scientific Nursing Journal done by Elsherbeny&Niazy (29) ,who…”
Section: A Pilot Studysupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a study done by Nayak et al (19) , who revealed that even with the The present study results were accordance with Moayed et al (28) study who reported that the level of stress among nurses are extremely multiplied by working with sharp objects. In agreement with study Tanta Scientific Nursing Journal done by Elsherbeny&Niazy (29) ,who…”
Section: A Pilot Studysupporting
confidence: 93%
“…Coppola et al (10) . indicated that about three Following the instructions on how to deal with patients and safe care can help decrease stress (11) .…”
Section: The Centers For Disease Control Andmentioning
confidence: 99%
“…20 The NPH zebrafish that developed in the presence of a daily stimulus, visual contact with a fish larger than itself, may have perceived it as a risk; since exposure to objects perceived as ''risky'' may cause higher stress response, such as increased stress levels in nurses by working with sharp objects. 21 Besides, Luca and Gerlai 22 found that the strongest fear responses were induced by images with the largest point size (among images of a sympatric predator, the Indian leaf fish, or a bird silhouette) shown to zebrafish, which were believed to interpret these stimuli as fast-approaching objects that could attack them. In addition, zebrafish preferred individuals that exhibited characteristics similar to their own (i.e., they exhibited a preference for conspecifics 23,24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jednak nie jest możliwe całkowite wyeliminowanie ostrych narzędzi medycznych z większości procedur medycznych. Na wystąpienie skaleczeń mogą mieć wpływ staż pracy, doświadczenie, atmosfera panująca w miejscu pracy, pośpiech, zdenerwowanie, stres, brak współpracy ze strony pacjentów i wiele innych czynników (6,7).…”
Section: Wstępunclassified
“…However, it is impossible to completely eliminate medical sharps from most medical procedures. The occurrence of cuts can be affected by work experience, experience, atmosphere in the workplace, haste, nervousness, stress, lack of cooperation on the part of patients and many other factors (6,7).…”
Section: Introductionmentioning
confidence: 99%